PENYUSUNAN BUKU PANDUAN PRAKTIK WISATA YANG BERTANGGUNG JAWAB DALAM PENDAKIAN GUNUNG - Masjhoer, Jussac Maulana; Wibowo, Dwi; Sadida, Bijak Qoulan; Ogista, Inosensius Tito (Kepariwisataan: Jurnal Ilmiah, 2017)
The lack of information related to the best practices in responsible tourism is one of the causes to tourist behavior problems. This study aims to determine the behavior of tourists in hiking, the adoption of responsible tourism practices, and to compile a responsible tourism practices guidebook. The research method used is survey research by spreading the questionnaire. Based on Likert analysis, at the pre-ascending stage, the classification of attitudes indicated by the respondents for cost and transportation is quite agreeable, while for equipment, guide, and simaksi is agreed. The ascent stage, the indicator when going up the mountain is quite agree, camping is not agree, the cook is agree, and when down the mountain is strongly agree. The post-ascent stage shows quite agreeable attitude. The public test of the guidebook, for the aspect of size and language of submission shows an agreeable attitude, while for the design, thickness, and content of the book shows an agreeable attitude. The conclusion is that (1) Still found the behavior of tourists in mountain climbing that is not environmentally friendly, (2) The responsible tourism practices of mountaineering that includes pre-ascending, ascent, and post-ascent, not well implemented by tourists, and (3) The responsible tourism practices guidebook still lack both technical and substance.